Pendidikan Kedokteran di Masa Pandemi COVID-19 Dampak Pembelajaran Daring Bagi Mahasiswa Fakultas Kedokteran Angkatan 2017 Unsrat - Rondonuwu, Vikny W. K.; Mewo, Yanti M.; Wungow, Herlina I. S. (Jurnal Biomedik : JBM, 2021)
Abstract: The world is currently heralded with a new outbreak, namely Corona Virus Disease 2019 (Covid-19).  In this situation, this online learning system is the right applied to be used in students of the Faculty of Medicine.  This study aimed to find out what impacts have the students of the Faculty of Medicine Batch of 2017 Sam Ratulangi Manado University in the application of online learning methods during the Covid-19 pandemic. This research is a qualitative method using the design of observation research and in-depth interviews conducted on 10 students of the Faculty of Medicine, Sam Ratulangi University obtained through purposive sampling techniques.  As a results, online learning is always dependent on internet connectivity, if there is problem with the internet connectivity it will have a considerable impact so that students can not attend lectures properly, in addition to the tools and supporting materials in the lab skill module is inadequate, and it is found that students do not have the readiness of psychology and devices in running online learning.  In conclusion, online learning has a quite complex impact on the learning process that occurs in students of the Faculty of Medicine, Sam Ratulangi University.Keywords: medical education, Covid-19 pandemic, online learning.  Abstrak: Dunia saat ini digemparkan dengan wabah yang baru, yaitu Corona Virus Disease 2019 (Covid-19).  Pada situasi ini, sistem pembelajaran daring merupakan terapan yang tepat digunakan termasuk pada mahasiswa Fakultas Kedokteran.  Tujuan penelitian ini untuk mengetahui apa saja dampak yang dimiliki Mahasiswa Fakultas Kedokteran Angkatan 2017 Universitas Sam Ratulangi Manado dalam penerapan metode pembelajaran daring di masa pandemi Covid-19.  Penelitian ini merupakan suatu penelitian dengan menggunakan metode kualitatif dengan rancangan penelitian observasi dan wawancara mendalam yang dilakukan pada 10 mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi yang diperoleh melalui teknik purposive sampling.  Hasil yang didapat, pembelajaran daring ini selalu bergantung pada konektivitas internet, jika konektivitas internet ini bermasalah maka akan memberikan dampak yang cukup besar sehingga mahasiswa tidak bisa mengikuti kuliah dengan baik, selain itu untuk alat dan bahan penunjang dalam modul skill lab tidak memadai, serta didapati mahasiswa tidak memiliki kesiapan psikologi dan device dalam hal mempersiapkan pembelajaran daring.  Sebagai simpulan, pembelajaran daring memberikan dampak yang cukup kompleks dalam proses pembelajaran yang terjadi pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi.Kata Kunci: pendidikan kedokteran, pandemi Covid-19, pembelajaran daring